The Safe Transport of Radioactive Waste by Using SAFRAN Program - Arkan Turki Al-Qaraghuli; Mohsen Abbas Mashai; Ismael Hashim Taher (Journal of Madenat Alelem University College, 2019)
In the present work study of the safety assessment by using SAFRAN program for safe transport of the radioactive waste containing radionuclide Cs137 from A city to B city after conditioning of radioactive waste by using ordinary Portland cement. The radiation dose was determined by radiometric measurements of all drums, all activities during the transfer process, determination of radiation exposure time, and the introduction of all data into the SAFRAN program. The calculations of the annual exposure value of workers and the public were obtained and the results were compared with the IAEA criteria in the normal operation and accident for protect human and environment during transportation.The result showed that the annual dose rate for all activities during transportation are less than the criteria limit ( 20 mSv for workers , 1.0 mSv for public ).